Kepemimpinan dan proses kerusakan hutan :: Studi tentang konflik peranan pemimpin tradisional dan pemerintah dalam pengelolaan hutan di Kabupaten Daerah Tingkat II Timor Tengah Utara Propinsi Nusa Tenggara Timur - MANEHAT, Paulus B (Universitas Gadjah Mada, 1998)
This study is to analysis the forest damage in Timor Island due to traditional leadership pattern change in forest management transformation into forest management in science way fiom government institution, population pressure and commerce. Timor Island was populated by some ethnic with their own cultures. However, 2 dominant cultures are Ema Tetun and Atoni Pah Meto. Both recognize and believe that forest is sacred and holly location, then the society members make a harmony relationship with the forest by ritual ceremony in order to not experience an incidence and the purpose is to consolidate the young generation to maintain and preserve the forest sacred value. The study areas were in 2 villages, Middle - Northern Timor Country, Te'ba, that represents Atoni culture; and N ah, that represents Tetun culture. The used method to get data w s administrative approach-document and participation study; a while the analysis method was descriptive-qualitative method, emphasizing policy analysis and supported by contextual analysis. From the study, it seems that the forest damage, especial sandal wood in Middle - Northern T h o r Country, is caused by governmental leadership pattern which could not ignore culture approach and less empowers the traditional institution: Tobe, that has, form generation to generation, managed the forest before the presence of village government. Tobe, as informal leader, has authority to perform the ritual ceremony and tax collection recognized by the local population up to present. This recognition is only one party, because the government as public policy maker does not recognize Tobe leadership, then a conflict fiequently occurs in managing the forest. This situation is used by local population living in and side of forest area, who are more and more dare to cut the forest o f stealing, and firing the f, forest to meet basic needs and finance secondary needs and facilitate the farming process. The radical thought and action developing in rural society life of Timor are individual anti- sandal movement, as an attitude to disagree the sandal exploitative yield sharing policy, which is profitable for the government. The forest product commerce, presence of a mature planning, based on a thought that any time the forest products, especial sandal wood, in Timor land, will be finished to cut off The forest management system or policy, which does not believe a traditional institution in Tobe t o lead the local society in managing the forest ,unequal sandal wood exploitative yield sharing, the confused sandal wood owner and insufficient apparatus discipline are government policy weakness, then it is necessary to present government attitude to believe in the local institution in managing the forest, while the government should be a facilitator, inspirator and donator, finally can be improved by the local society are for economic development and people prosperity improvement.